If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -2y + -3y + -6 = 0 Reorder the terms: -6 + Y + -2y + -3y = 0 Combine like terms: -2y + -3y = -5y -6 + Y + -5y = 0 Solving -6 + Y + -5y = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + Y + 6 + -5y = 0 + 6 Reorder the terms: -6 + 6 + Y + -5y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + Y + -5y = 0 + 6 Y + -5y = 0 + 6 Combine like terms: 0 + 6 = 6 Y + -5y = 6 Add '5y' to each side of the equation. Y + -5y + 5y = 6 + 5y Combine like terms: -5y + 5y = 0 Y + 0 = 6 + 5y Y = 6 + 5y Simplifying Y = 6 + 5y
| .05c=.08+7.50 | | x+5=5x+25 | | y-(-5)=-6(x-1) | | 2x-71.50=4308.50 | | x+(x+5)+(2x+11)=180 | | 3/4y-6=0 | | x-20+x= | | 695=13(k+5)+32 | | logx=0.45 | | 7b=85 | | 10(g-836)=740 | | 5x-5(-6-2x)=0 | | 5-7x=2x+8 | | 2-2y-3y=0 | | 9x-(3x+3)=4x-49 | | -2=6-x | | 29=2+3g | | 8(4w+9)=-8 | | 4x^2-11x+15=0 | | 9r+8s-5(8r-5s)= | | 3x^2+12x-24=-26 | | 1/3x^2-1/12x-1/6=0 | | 803=792-b | | -6(q-81)=-30 | | 4.3(4+2x)-4.2=13 | | 2(8x+4)=22x | | -10(s+5)=-101 | | Ln(5/x)=-2 | | k^2-4k-2=0 | | 9x+8y-5(8x-5y)= | | 3(s+11)+22=76 | | 4(3p+1)=64 |